Culture barbariche, modelli ecclesiastici, tradizione romana nell'Italia longobarda e franca Barbarian culture, ecclesiastical pattern, Roman tradition in the Lombard and Frankish Italy - Stefano Gasparri (Reti Medievali Rivista, 2005)
Propone una sintesi aggiornata sui principali problemi politici, religiosi e culturali dell’Italia dei secoli VIII-IX: l’evoluzione della religiosità dei longobardi dall’arianesimo al progressivo inquadramento cattolico e la difficile integrazione tra longobardi e latini e franchi. Una attenzione particolare è rivolta ai longobardi dell’Italia meridionale. This study offers an updated synthesis of the main political, religious and cultural issues in 8th and 9th century Italy. In particular, it examines the progressive transition of the Longobard religious faith from Arianism to Catholicism, and the troubled integration of Lombards, Latins and Franks. Special attention is paid to Lombards’ riots in southern Italy.